Perspectives of Agroforestry Practitioners on Agroforestry Adoption: Case Study of Selected SARE Participants. (20th September 2022) - Romanova, Olga; Gold, Michael A.; Hall, Damon M.; Hendrickson, Mary K.
Abstract: Agroforestry practices offer a compelling addition to conventional agriculture as they provide a broad range of economic, ecological, and social benefits. Despite its recognized potential, broad on‐the‐ground adoption of U.S. agroforestry remains limited. Factors influencing agroforestry adoption and dissemination bottlenecks by actual practitioners are underexplored. While previous studies have focused mostly on landowner and farmer interests in agroforestry, without them necessarily being practitioners, this research details the perspective of those who have actively implemented some agroforestry practices. Early adopters of agroforestry represent an essential catalyst for future agroforestry diffusion. Better understanding of the factors influencing their decisions and reasons behind agroforestry practice adoption will help to support and promote wider adoption. This research study documents the what and why questions of early‐stage agroforestry adoption and the intrinsic and extrinsic factors that influence both adoption and discontinuation decisions. Recommendations are offered to target and attract more agroforestry practitioners.